Geopolitics And Its Impact On The Indonesian Economy In The Era Of Globalization - Valhan Hamdiana Rachman (Jurnal Ekonomi, 2024)
This study aims to analyze the relationship between global geopolitical dynamics and its impact on the Indonesian economy in the era of globalization. Geopolitics, as the study of the influence of political power on territory and resources, is increasingly playing a strategic role in determining a country's economic stability and growth. In the era of globalization, technological advances, and changes in the world order are accelerating changes in geopolitical relations, which have direct implications for the economic sector, including trade, investment, and energy security. This research uses a qualitative-descriptive approach. The results of this study show that geopolitics has a significant impact on the Indonesian economy, both in terms of trade, investment, the maritime sector, and tourism. Global geopolitical instability, such as international tensions and protectionist policies, can disrupt international trade routes, increase logistics costs, and affect the flow of foreign investment to Indonesia. In addition, disruptions to Indonesia's maritime security, such as smuggling of goods and overlapping territorial claims, have the potential to harm economic sectors that depend on natural resources and maritime transportation. On the other hand , geopolitical tensions have also had an impact on the decline in the number of foreign tourists, which has an impact on the decline in Indonesia's tourism sector revenue. Overall, this study underlines the importance of geopolitical stability in ensuring the sustainability and growth of the Indonesian economy amidst changing global dynamics.